KUALITAS PELAYANAN RUMAH SAKIT UMUM DAERAH dr. H. ANDI ABDURRAHMAN NOOR KABUPATEN TANAH BUMBU - Ade Hermawan; Bakhtiar Bakhtiar (AL-ULUM : Jurnal Ilmu Sosial dan Humaniora, 2022)
Five indicators are used as a measure to analyze the services of the Regional GeneralHospital dr. H. Andi Abdurrahman Noor Tanah Bumbu Regency, namely theconvenience of service facilities, service accuracy, friendliness of officers, punctuality,and ease of service procedures all have a good tendency, meaning that it can beconcluded that the quality of services provided by the Regional General Hospital dr. H.Andi Abdurrahman Noor Tanah Bumbu Regency is qualified.